PENGARUH PRODUK, HARGA, LOKASI DAN PELAYANAN TERHADAP KEPUTUSAN PASIEN UNTUK MELAKUKAN PEMERIKSAAN DI LABORATORIUM KLINIK SETIA LABORA KOTA PAYAKUMBUH. - Sastrismal Sastrismal; Yasri yasri (Jurnal Riset Manajemen Bisnis dan Publik, 2014)
The purpose of this study was to analyze the effect of product, price, place and Patient Care Against Decision To Conduct Examination In Clinical Laboratory Faithful Labora Payakumbuh. This type of research is causative, where the research was to analyze the effect of one variable with another variable. As the population in the study were patients who came to the laboratory examination Clinical Laboratory Labora Faithful. The research sample was taken with accidental sampling technique. The sample size was determined using the formula of Cooper and Emory. In this study, the sample size was 94 patients for the study comprised of 51 men and 42 women .. Research data sourced from primary data obtained from questionnaires submitted to respondent. Data analysis techniques using descriptive and inductive analysis through regression analysis. Hypothesis testing using t-test at α = 0.05. The results showed that: (1) Product Variables significantly influence the decision to choose the laboratory to examine the sig = 0.022 (2) Variable price significantly influence the decision to choose the laboratory to examine the sig = 0.001. (3) The variables significantly influence the decision to choose the laboratory for examination with variable sig = 0.009 and significant service to the patient's decision in choosing a laboratory to conduct spot checks with sig = 0.024. KeyWordrs : Patient Decision to Conduct Examination